Comprehensive Behavioral Therapy of Trichotillomania: A Multiple-Baseline Single-Case Experimental Design - Bottesi, Gioia; Ouimet, Allison Jane; Cerea, Silvia; Granziol, Umberto; Carraro, Eleonora; Sica, Claudio; Ghisi, Marta (Frontiers in Psychology, 2020)
Despite rapidly increasing knowledge about Trichotillomania (TTM), no gold-standard evidence-based psychological intervention has been identified. In the current study, we evaluated the potential efficacy of an 8-session psychological intervention for TTM, namely the Comprehensive Behavioral Model (ComB) treatment, using a multiple-baseline single-case experimental design with 3 Italian women with TTM. The study included 3 phases: baseline, intervention, and 3-month follow-up. We assessed the intervention using daily self-monitoring of number of hair-pulling episodes, number of pulled hairs per episode, degree of resistance to pulling urges, and degree of associated distress. We also assessed for reliable improvement in general distress from baseline to post-intervention. All participants completed treatment and showed improvements on those symptom measures that were most relevant to their individualized case conceptualization. However, no participants recovered completely or demonstrated reliable improvement in general distress. Our results provide initial evidence for the utility of the ComB treatment for TTM in an Italian clinical setting. Furthermore, they support the delivery of individualized and flexible psychological treatments when treating TTM.